Lumbar osteomyelitis and knee septic arthritis caused by Streptococcus agalactiae bacteraemia. Issue 4 (19th April 2022) - Gaffaney, Lauren; McKee-Proctor, Maxwell; Yeung, Ho-Man
Abstract : A man in his late 70s presented to the emergency department endorsing a week of malaise. He was recently hospitalised for 2 days for new back pain and was discharged with non-opioid pain medications but continued to seek care as he felt unwell. On presentation, he was afebrile with a leukocytosis. Physical examination revealed a painful left knee with no evidence of trauma. Arthrocentesis revealed purulent fluid with elevated white blood cell consistent with septic arthritis. He was started on broad-spectrum antibiotics and underwent irrigation and synovectomy of the left knee. Aspirate and blood cultures grew Streptococcus agalactiae . Transthoracic echocardiogram showed no vegetations; however, an MRI of lumbar spine showed L2–L3 and L4–L5 osteomyelitis. He was treated with intravenous ceftriaxone for 3 weeks and then oral levofloxacin for 3 weeks, for a total 6 week course of antibiotics.